Psychotherapists’ self-protective attachment strategies - Giannotti, Michele; Crittenden, Patricia; Landini, Andrea; Lambruschi, Furio (Frontiers in Psychology, 2025)
Attachment describes how people use relationships to cope with exposure to danger. That function is central to psychotherapy. This study used the Adult Attachment Interview (DMM-AAI) to compare psychotherapists’ attachment strategies to those of patients in psychotherapy and adults drawn from the normative non-patient population. The central variables were attachment strategies (treated as dismissing of relationships Type A1-8, secure/balanced in relationships B1-5, and preoccupied with relationships Type C1-8, plus A/C combinations), psychological trauma and unresolved loss, extremes of arousal, and reorganization toward psychological balance and integration (i.e., conscious change toward B strategies). Differences based on professional training (psychodynamic, cognitive, and family systems) were explored for psychotherapists. The results indicated that non-patients demonstrated the lowest risk attachment strategies (i.e., A1-2, B1-5, and C1-2), whereas patients exhibited the highest risk and most extreme attachment strategies (i.e., A5-8, C5-8, and A5-8/C5-8), and the most psychological trauma, unresolved loss, and extreme arousal. Psychotherapists were not a homogeneous group: approximately 40% showed extreme attachment strategies, whereas the remainder demonstrated low-risk strategies. A higher proportion of psychotherapists (24.6%) showed reorganization toward B strategies than patients (6.8%); this replicates earlier work on British psychotherapy students and patients. Trauma and loss were significantly more frequent in both patients and psychotherapists than in non-patients. No differences were identified based on psychotherapists’ theory training. These findings suggest that more than half of Italian psychotherapists have the potential to establish intersubjectivity with their patients whereas almost half might face problems reaching beyond their personal perspective. Suggestions for improving training and supervision of psychotherapists are offered.